Jenseits des vereinten Europas: rechtsextreme Parteien in Tschechien und der Slowakei - Novotny, Lukas; Thieme, Tom (2010)
Abstract: "Despite the generally positive transformation in East Central Europe, there are still participants in politics connecting to the totalitarian inheritance of the past. This essay examines the causes, effects and developments of rightwing extremism in the Czech Republic and in Slovakia from a comparative perspective. Although both countries have much in common as far as historical and current causes for the development of extremism are concerned, they differ particularly in the extent of right- and left-wing extremism. While the Czech Republic's extreme left-wing KSCM achieved two-digit results in all national elections, since more than one decade right-wing extremist organizations have almost disappeared from the political stage. Meanwhile in Slovakia, by the SNS there exists one of the most successful right-wing extremist parties of Europe, while the orthodox communists are not at all as successful as their Czech comrades. Nevertheless, there are common grounds also beyond the ext